Navigating trade-offs between dams and river conservation. (10th August 2021) - Thieme, M.L.; Tickner, D.; Grill, G.; Carvallo, J.P.; Goichot, M.; Hartmann, J.; Higgins, J.; Lehner, B.; Mulligan, M.; Nilsson, C.; Tockner, K.; Zarfl, C.; et al.
Abstract : Non-technical summary: There has been a long history of conflicts, studies, and debate over how to both protect rivers and develop them sustainably. With a pause in new developments caused by the global pandemic, anticipated further implementation of the Paris Agreement and high-level global climate and biodiversity meetings in 2021, now is an opportune moment to consider the current trajectory of development and policy options for reconciling dams with freshwater system health. Technical summary: We calculate potential loss of free-flowing rivers (FFRs) if proposed hydropower projects are built globally. Over 260, 000 km of rivers, including Amazon, Congo, Irrawaddy, and Salween mainstem rivers, would lose free-flowing status if all dams were built. We propose a set of tested and proven solutions to navigate trade-offs associated with river conservation and dam development. These solution pathways are framed within the mitigation hierarchy and include (1) avoidance through either formal river protection or through exploration of alternative development options; (2) minimization of impacts through strategic or system-scale planning or re-regulation of downstream flows; (3) restoration of rivers through dam removal; and (4) mitigation of dam impacts through biodiversity offsets that include restoration and protection of FFRs. A series of examples illustrate how avoiding or reducing impacts on rivers is possible – particularly when implemented at a system scale – and can be achieved while maintaining or expanding benefits for climate resilience, water, food, and energy security. Social media summary: Policy solutions and development pathways exist to navigate trade-offs to meet climate resilience, water, food, and energy security goals while safeguarding FFRs.